Review of the huntsman spider genus Rhitymna Simon, 1897 (Araneae: Sparassidae) - Jäger, Peter (Zootaxa, 2019)
The genus Rhitymna Simon, 1897 is revised by means of new material. Four new species are described: R. gerdmangel spec. nov. (Thailand, Malaysia; male, female), R. merianae spec. nov. (Indonesia: Bali; male), R. flores spec. nov. (Indonesia: Flores; male, female), R. senckenbergi spec. nov. (Philippines; male). The male of R. plana Jäger, 2003 and the female of R. tangi Quan & Liu, 2012 are described for the first time. Rhitymna simoni Jäger, 2003 is recognised as junior synonym of R. cursor (Thorell, 1894) comb. nov., the latter transferred from the genus Olios Walckenaer, 1837. New records are given for further Rhitymna species, among them new country or island records for R. verruca (Wang, 1991) (Thailand), R. tangi Quan & Liu, 2012 (Laos), R. plana Jäger, 2003 (Cambodia), R. pinangensis (Thorell, 1891) (Thailand), R. deelemanae Jäger, 2003 (Bali). The number of cheliceral bristles close to the fang base is recognised as size dependent, therefore without true phylogenetic signal. Two main types of copulatory organs within the genus are recognised and discussed. R. gerdmangel spec. nov. has a special biology as it lives exclusively in bamboo. Holes made by beetles or woodpeckers are used to enter the bamboo stem. Spiders hide during the day and lay their eggs in bamboo internodes.